Legislatures, legislation and legislating in the british atlantic, 1692–1800 - Graham, A (Wiley, 2018)
Despite recent work quantifying the legislative output of the British and Irish parliaments between 1692 and 1800, the same has not been extended to the imperial territories of the British Atlantic in the same period, despite the importance of colonial politics in the sweeping constitutional changes that culminated in 1775 and revolution. This article is the first to track the basic patterns of legislative output from all the colonial legislatures in north America and the West Indies and to link these data with population. It shows that the overall output jumped considerably in the period, as in Britain and Ireland, but that this was largely concentrated in the 1750s and 1760s under the pressure of warfare, though colonial elites afterwards began to exploit their new legislative experience for their own needs. However, no clear correlation was found between legislation and revolution. The experience of individual territories varied wildly, suggesting that the causes of revolution were neither inherent nor inevitable, and that legislation was a tool used by both sides rather than a cause of conflict in its own right.